Preliminary Study of an Integrated Calculation of Ship Strength on Tankers with Applicable Regulations - Yulianto, Ardi Nugroho; Putra, Erzad Iskandar; Hermawan, Yuda Apri; Putranto, Teguh; Ahadyanti, Gita Marina; Sujiatanti, Septia Hardy; Utama, Danu; Siswantoro, Nurhadi; Zidni, Irfan; Hadi, Herry Sufyan (International Journal of Offshore and Coastal Engineering (IJOCE), 2023)
Recently, the development of the digital era has increased significantly. Industry 4.0 began to be discussed and applied in the early 21st century. Cyber-Physical systems are becoming a trend in current technological developments. Several technologies in Industry 4.0 are being applied, such as the internet of things, cloud computing, automated simulation, intelligent robots, big data analysis, augmented reality, and additive manufacturing. The shipyard industry is one industry that must be able to adapt to keep up with technological developments. In the ship's preliminary design stage, the strength calculation process that refers to certain regulations has an important role in the design process. The integrated calculation system will make working easier for a naval architect. This paper aims to conduct an initial study in calculating ship strength integrated in real-time with the regulations that govern it. This study produces an idea to integrate the calculation of ship strength with regulations from a class society that continues to grow. The research is expected to provide further development to assist in the preliminary design process that provides efficiency and more accurate monitoring of results.